Usefulness of Intraoperative Neurophysiological Monitoring During the Clipping of Unruptured Intracranial Aneurysm: Diagnostic Efficacy and Detailed Protocol - Park, Dougho; Kim, Byung Hee; Lee, Sang-Eok; Jeong, Eunhwan; Cho, Kwansang; Park, Ji Kang; Choi, Yeon-Ju; Jin, Suntak; Hong, Daeyoung; Kim, Mun-Chul (Frontiers in Surgery, 2021)
Background: Intraoperative neurophysiological monitoring (IONM) has been widely applied in brain vascular surgeries to reduce postoperative neurologic deficit (PND). This study aimed to investigate the effect of intraoperative neurophysiological monitoring (IONM) during clipping of unruptured intracranial aneurysms (UIAs). Methods: Between January 2013 and August 2020, we enrolled 193 patients with 202 UIAs in the N group (clipping without IONM) and 319 patients with 343 UIAs in the M group (clipping with IONM). Patients in the M group were intraoperatively monitored for motor evoked potentials (MEPs) and somatosensory evoked potentials (SSEPs). Irreversible evoked potential (EP) change was defined as EP deterioration that did not recover until surgery completion. Sustained PND was defined as neurological symptoms lasting for > 1 postoperative month. Results: Ten (3.1%) and thirteen (6.7%) in the M and N groups, respectively, presented with PND. Compared with the N group, the M group had significantly lower occurrence rates of sustained PND (odds ratio [OR], 0.36; 95% confidence interval [CI], 0.13−0.98; p = 0.04), ischemic complications (OR, 0.39; 95% CI, 0.15−0.98; p = 0.04), and radiologic complications (OR, 0.40; 95% CI, 0.19−0.82; p = 0.01). Temporary clipping was an independent risk factor for IC in the total patient group (OR, 6.18; 95% CI, 1.75−21.83; p = 0.005) but not in the M group (OR, 5.53; 95% CI, 0.76−41.92; p = 0.09). Regarding PND prediction, considering any EP changes (MEP or/and SSEP) showed the best diagnostic efficiency with a sensitivity of 0.900, specificity of 0.940, positive predictive value of 0.321, negative predictive value (NPV) of 0.997, and negative likelihood ratio (LR) of 0.11. Conclusion: IONM application during UIA clipping can reduce PND and radiological complications. The diagnostic effectiveness of IONM; specifically, the NPV and LR negative values, was optimal upon consideration of changes in any EP modality.